Nutritional analysis, metabolomics and proteomics of edible bird nest from different georaphical regions of Malaysia - Zulkifli, Danish Adli (2018)
Edible bird’s nest (EBN) is made of the salivary secretions from the swiftlet species Aerodramus fuciphagus. It is well-known in traditional Chinese medicine as well as among Asian countries due to their beneficial effects on health. Previous studies have shown that consumption of EBN provides various health benefits such as promoting epidermal growth, inhibiting infection caused by influenza viruses and others. Nowadays EBN is prepared and incorporated into many food products including drinks, food additives and cosmetics. Despite the continuous demand on EBN, strong justification on the nutritional and medicinal benefits of the farmed and commercialised EBN is still lacking. This study compared the chemical, amino acid, mineral constituents and the metabolites and protein profiles using proteomic and metabolomic approaches between the commercialised EBN bought from a reputable drug store and farmed EBN collected from the Central, Southern, East Coast and East of Malaysia. The chemical composition of the EBN was determined according to the Food Analysis Laboratory Manual with slight modifications. The elemental analysis was done in accordance of the official AOAC method. The detection of amino acid was done with High Performance Liquid Chromatography (HPLC) with Pico-Tag Amino Acid Analysis Column. 1H-Nuclear Magnetic Resonance (NMR) spectroscopy was then used to detect the metabolites in the EBNs while Chemomx NMR Suite 8.2 was used to analyse the detected metabolites. The analysis of the EBN’s proteome was done through the use of two-dimensional gel electrophoresis (2-DGE) followed by matrix assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF/TOF MS). The results showed that the farmed EBN was mainly comprised of protein followed by carbohydrate while the commercial EBN had similar protein and carbohydrate composition. The total amount of essential amino acid in commercial EBN was higher (237.9 mg/g protein) compared to the farmed EBN (156.81 –236.6 mg amino acid/ g protein) with valine the highest found in both the farmed and commercialised EBN. For the elemental analysis, both farmed and commercialised EBN were found to have a good amount of calcium and potassium content. There were 26 metabolites identified and phenylalanine; an essential amino acid was found significantly in abundance in all farmed EBN but not in commercialised EBN. In addition, choline; a vitamin-like essential nutrient and acetic acid were also found in large amount in all farmed EBN while acetone and 3-hydroxyisovaleric acid were found high in commercialised EBN. A number of metabolites from chemical classes such as organic acids and amino acids were identified from the use of NMR spectroscopy. The proteins detected through the proteomic process includes complement C1q, alpha-(1,3)-fucosyltranferase 6, glutamine-rich protein and tropomyosin alpha-1 chain. The complement C1q is known to involve in the clearance of apoptotic cells and pathophysiology of the central nervous system while alpha-(1,3)-fucosyltranferase 6 involved in the protein glycosylation pathways. Tropomyosin alpha-1 chain involved in the regulation of the straited muscle contraction. The overall findings suggested that the nutritional analysis, metabolites profiling and the proteomic analysis can give a better understanding about Malaysian EBN, benchmarking procedure and quality determination of EBN in the future.